Antibasal Ganglia Antibodies and Antistreptolysin O in Noncomorbid ADHD. (November 2015) - Toto, Maddalena; Margari, Francesco; Simone, Marta; Craig, Francesco; Petruzzelli, Maria Giuseppina; Tafuri, Silvio; Margari, Lucia
Objective: An association between streptococcal infections, ABGA positivity, and no comorbidity ADHD (nc-ADHD) has been little investigated. The aim of this study was to evaluate the streptococcal infection frequency, defined entitled serum antistreptolysin O (ASO), and frequency of serum ABGA positivity in a sample of patients with nc-ADHD.Method: In all 40 participants were investigated the ASO titer and ABGA.Results: The results showed that ABGA positivity was statistically significantly higher in patients affected by ADHD than in patients of a control group, and pathological values of ASO were statistically more frequent in the ADHD group than the control group.Conclusion: These data suggest that streptococcal infections and autoimmune reactions against the basal ganglia are more frequent in ADHD patients than patients in a control group.